Pengaruh Penerapan Teknik Rileksasi terhadap Peningkatan Kemampuan Konsentrasi Siswa - Jajat Darajat Kusumah Negara; Titik Syadiah (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2018)
The purpose of this study was to determine and to analyze the effect of the implementation of Jacobsen’s progressive relaxation techniques and Schulte software concentration training on improving students' concentration ability. The method used was experimental method by using the pre-postest group design. The population in this study were 7th and 8th grade junior high school students in Bandung. The sample in this study were 70 students. The sampling technique used was proportional stratified random sampling which was divided into two groups: 35 students into Jacobsen's relaxation group and 35 students into the concentration training group. The result of the study concludes that there was significant improvement in concentration ability (51.23%) by applying Jacobsen's progressive muscle relaxation technique; secondly, there was significant improvement in the ability to concentrate (37.69%) by applying Schulte software concentration training; the last, there was no significant difference in concentration ability between the group accepting Jacobsen's muscle relaxation technique and the group accepting Schulte software concentration training. AbstrakTujuan penelitian ini untuk mengetahui dan menganalisis pengaruh  penerapan teknik rileksasi progresif jacobsen dan latihan konsentrasi software schulte terhadap peningkatan kemampuan konsentrasi siswa. Metode yang digunakan adalah metode ekperimen dengan menggunakan desain Pre-postest Group Design. Populasi pada penelitian ini adalah siswa siswi kelas VII dan VIII SMP Negeri 9 Bandung berjumlah 70 siswa. Teknik pengambilan sampel menggunakan  Proportionate Stratified Random Sampling yang dibagi ke dalam dua kelompok yaitu 35 siswa ke dalam  rileksasi Jacobsen, dan 35 siswa pada kelompok latihan konsentrasi. Hasil penelitian menunjukan terdapat peningkatan kemampuan konsentrasi sebesar 51,23% dengan menerapkan teknik rileksasi otot progresif Jacobsen. Sedangakan penerapan software schulteterdapat meningkatkan kemampuan konsentrasi 37,69%. Tidak ada perbedaan kemampuan konsentrasi antara penerapan teknik rileksasi otot Jacobsen dengan penerapan software schulte.